2008 38th Annual Frontiers in Education Conference 2008
DOI: 10.1109/fie.2008.4720595
|View full text |Cite
|
Sign up to set email alerts
|

Important student misconceptions in mechanics and thermal science: Identification using Model-Eliciting Activities

Abstract: -As any engineering faculty member teaching undergraduates knows, students possess a wide variety of misconceptions about fundamental engineering concepts. In the thermal sciences, there are numerous misconceptions about heat, energy, and temperature; mechanics students hold misconceptions about inertia, angular velocity, and energy. This is complicated by the fact that we possess many years of everyday experiences with energy flows, forces, and kinematics. Due to previous experiences, it is often difficult to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 11 publications
2
30
0
2
Order By: Relevance
“…Students in college level science (Jasien & Oberem, 2002) and engineering programs (Miller et al, 2006;Prince & Vigeant, 2006;Self et al, 2008) had been found to hold multiple misconceptions about heat, temperature, and energy. For example, Prince and Vigeant (2006) found that many engineering undergraduates viewed heat and temperature as equivalent entities while Self et al (2008) determined that almost 30% of chemical and mechanical engineering seniors could not understand "… Logically distinguish between temperature and energy in simple engineering systems and processes" (p. S2G-1).…”
Section: Misconceptions About Heat Temperature and Energymentioning
confidence: 99%
See 3 more Smart Citations
“…Students in college level science (Jasien & Oberem, 2002) and engineering programs (Miller et al, 2006;Prince & Vigeant, 2006;Self et al, 2008) had been found to hold multiple misconceptions about heat, temperature, and energy. For example, Prince and Vigeant (2006) found that many engineering undergraduates viewed heat and temperature as equivalent entities while Self et al (2008) determined that almost 30% of chemical and mechanical engineering seniors could not understand "… Logically distinguish between temperature and energy in simple engineering systems and processes" (p. S2G-1).…”
Section: Misconceptions About Heat Temperature and Energymentioning
confidence: 99%
“…For example, Prince and Vigeant (2006) found that many engineering undergraduates viewed heat and temperature as equivalent entities while Self et al (2008) determined that almost 30% of chemical and mechanical engineering seniors could not understand "… Logically distinguish between temperature and energy in simple engineering systems and processes" (p. S2G-1). Related content areas which have been recurrently problematic for engineering students have included factors that affect the rate and amount of heat transferred, distinctions between temperature and energy, differences between temperature and perceptions of hot/cold, and the effects of surface properties on heat transfer by radiation (Miller et al, 2006;Prince & Vigeant, 2006).…”
Section: Misconceptions About Heat Temperature and Energymentioning
confidence: 99%
See 2 more Smart Citations
“…Despite completing several courses in thermal and transport sciences, a significant number of students have misconceptions about simple heat transfer processes 2,3,4 . Through the development of the "Thermal and Transport Concept Inventory" (TTCI) test 5 , it has been observed that students possessed "robust misconceptions" about the differences between  heat, energy and temperature,  rate and amount of transfer (e.g., heat transfer, momentum transfer, mass transfer), and  steady-state and equilibrium processes 6 .…”
Section: Introductionmentioning
confidence: 99%